Kejelasan Sasaran Anggaran, Akuntabilitas Publik, Kompetensi, dan Evaluasi Anggaran pada Kinerja Manajerial di OPD Kabupaten Pelalawan - Rofika; Rahmadani, Alya Dwi; Basri, Yesi Mutia (Muhammadiyah Riau Accounting and Business Journal, 2020)
This study aims to examine and analyze the effect of the Budget Targets Clarity, Public Accountability, Competence, and Budget Evaluation on Managerial Performance in Regional Apparatus Organization Pelalawan. The population in this study are civil servant who have a structural position and apparatus who have a role in budgeting at every Regional Apparatus Organization Pelalawan. The collecting data using primary data obtained from questionnaires by using purposive sampling technique. The sample in this study consists of a leaders who held position as head of the Regional Apparatus Organization, secretary or secretary level, and head of the finance sub section the total is 84 people. The results showed that the clarity of the budgetary target, public accountability, competence, and budget evaluation influences on managerial performance.